(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
Bilateral Optic Neuritis (ON) is an alarming feature for the patient and not commonly faced by clinicians. Acute Disseminated Encephalomyelitis (ADEM) is a demyelinating disease that commonly underdiagnosed due to features sharing that of stroke. But progressive clinical course, behavioral change, features of bilateral Upper Motor Neuron (UMN) lesion, convulsion, bilateral optic neuritis (Sometimes unilateral) can help clinician to think quickly that ADEM could be a possibility. Among its clinical presentation optic neuritis is least common (6%) whereas behavioral change is universal (100%). Acute disseminated encephalomyelitis is suspected in this adult male patient because of progressive painful visual impairment, urinary retention, limb weakness which were associated with behavioral change. After clinical evaluation and relevant investigations he was diagnosed as a case of ADEM, & treated with intravenous methylprednisolone followed by oral prednisolone. During follow up (After 9 weeks) his symptoms and signs improved about 80% whereas MRI lesions regressed about 50%. JCMCTA 2015 ; 26 (2) : 77 - 78